An Overview of the MUSES Calculation Engine and How It Can Be Used to Describe Neutron Stars - Mateus Reinke Pelicer; Veronica Dexheimer; Joaquin Grefa (Universe)
For densities beyond nuclear saturation, there is still a large uncertainty in the equations of state (EoSs) of dense matter that translate into uncertainties in the internal structure of neutron stars. The MUSES Calculation Engine provides a free and open-source composable workflow management system, which allows users to calculate the EoSs of dense and hot matter that can be used, e.g., to describe neutron stars. For this work, we make use of two MUSES EoS modules, i.e., Crust Density Functional Theory and Chiral Mean Field model, with beta-equilibrium with leptons enforced in the Lepton module, then connected by the Synthesis module using different functions: hyperbolic tangent, generalized Gaussian, bump, and smoothstep. We then calculate stellar structure using the QLIMR module and discuss how the different interpolating functions affect our results.